Monitoring Land Cover Variation Using Some Spectral Indicators in Akre Region Based on Geospatial Techniques - Shaymaa Akrawi; Khaled Alkhaled (Mesopotamia Journal of Agriculture)
The study was carried out in the Aqre area of northern Iraq, which represents lands with various agricultural uses and located between latitudes (37°2ˉ5.42˭ - 36°29ˉ59.26˭) N and longitudes (43°35ˉ56.84˭ -44°18ˉ31.56˭) E to study the spectral indices (SI, NDSI, OSAVI, OVI, GDVI2) related to soil salinity and vegetation cover for three years (2003, 2013, 2023) based on Landsat satellite data (7, 8, 9) to diagnosing salinity-affected soils and monitoring changes in land use. (40) Surface soil samples were collected with different agricultural uses and were prepared for laboratory analysis. The results showed that the pH values were characterized by being moderate in most of the sites. The Ec values ranged between (0.12-1.24) dS m-1, and the CaCO3 content ranged between (110-460). g kg-1. The results showed that the CEC values ranged between (16.03-37.81) Cmolkg-1.The results indicated that the area affected by salinity in 2003 and represented by the presence of five SI classes, as their values ranged from lowest value (57.688 - 69.777) to the highest value (82.908 - 110.837). Result showed decline in vegetation over three years was caused by the effect of climate, particularly rainfall. indicating that the lands are now under strong agricultural management, since the majority of the percentages in the areas of the types were greater in 2013 than in the previous two years. also keep in mind that the largest percentages were for the best variation for each index, reaching (39.772%, 22.683%, 18.397%, 11.400%) for SI, NDSI, OSAVI, and EVI, respectively.